Ultrasensitive Impedimetric Lectin Biosensor with Efficient Antifouling Properties Applied in Determination of a-Fetoprotein on Mixed Self-Assembled Monolayer on Gold - Yang, Haiying; Gong, Qiaojuan; Ma, Lina; Sun, Yuanlin; Zhang, Wenchan (Asian Journal of Chemistry, 2014)
A sensitive and attractive antifouling impedimetric lectin biosensor for the determination of a-fetoprotein in human serum samples was developed. The biosensor was fabricated by co-assembling 11-mercapto-undecanoic acid for covalent immobilization of wheat-germ agglutinin and dithiothreitol to resist nonspecific interactions on the surface of gold electrode. In the measurement of a-fetoprotein, the change in interfacial electron transfer resistance of biosensor was monitored using a ferri/ferrocyanide redox couple. Owing to the specific recognition of wheat-germ agglutinin with N-glycan on a-fetoprotein, the increase in the electron transfer resistance was linearly proportional to the logarithm of the concentration of a-fetoprotein in the range from 1.0 × 10-11 to 8 × 10-10 g mL-1 and a detection limit of 9 × 10-12 g mL-1 a-fetoprotein was achieved. The fabricated biosensor allowed direct quantification of extrinsic a-fetoprotein in serum samples. This work provides a promising strategy for clinical application with impressive sensitivity and antifouling characteristics.